In-line optofluidic refractive index sensing in a side-channel photonic crystal fiber - Dinh, Xuan Quyen (2017)
An in-line optofluidic refractive index (RI) sensing platform is constructed by splicing a side-channel photonic crystal fiber (SC-PCF) with side-polished single mode fibers. A long-period grating (LPG) combined with an intermodal interference between LP01 and LP11 core modes is used for sensing the RI of the liquid in the side channel. The resonant dip shows a nonlinear wavelength shift with increasing RI over the measured range from 1.3330 to 1.3961. The RI response of this sensing platform for a low RI range of 1.3330-1.3780 is approximately linear, and exhibits a sensitivity of 1145 nm/RIU. Besides, the detection limit of our sensing scheme is improved by around one order of magnitude by introducing the intermodal interference.